Facility location : concepts, models, algorithms and case studies - Zanjirani Farahani, Reza.; Hekmatfar, Masoud (Berlin : Physica-Verlag, 2009)
This book deals with location problems. Location problems establish a set of facilities (resources) to minimize the cost of satisfying a set of demands (customers) with respect to a set of constraints. There are four components that describe location problems: customers, who are assumed to be already located at points or on routes, facilities that will be located, a space in which customers and facilities are located, and a metric that indicates geographical and chronological distances between customers and facilities. This book describes these parts in each specific location model. Location models are used in a variety of applications such as locating warehouses within a supply chain to minimize the average time to market, locating noxious material to maximize its distance to the public, et cetera In this book, readers can find these applications exemplified by real-world cases for each particular model. The relationship between location problems and other areas such as supply chains is also considered here.
-- Distance Functions in Location Problems -- An Overview of Complexity Theory -- Single Facility Location Problem -- Multifacility Location Problem -- Location Allocation Problem -- Quadratic Assignment Problem -- Covering Problem -- Median Location Problem -- Center Problem -- Hierarchical Location Problem -- Hub Location Problem -- Competitive Location Problem -- Warehouse Location Problem -- Obnoxious Facility Location -- Dynamic Facility Location Problem -- Multi-Criteria Location Problem -- Location-Routing Problem -- Storage System Layou t-- Location-Inventory Problem -- Facility Location in Supply Cha -- Classification of Location Models and Location Softwares -- Demand Point Aggregation Analaysis for Location Models.
Includes biliographical references and index.
Keywords: Industrial location -- Decision making -- Mathematical models